Systematic review and classification of: SMIL - Enhanced coping in life (2. ed.) - Vis, Svein Arild; Havnen, Karen J. Skaale (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2017)
Background: This article is a systematic review of current knowledge of the effects of the program SMIL. The article is a revision of a previous paper on this intervention in Ungsinn (Vis, 2011). The program is a group based psychoeducational program for children aged 8-12 years old, who have a parent with a mental health and/or substance abuse problem. The aim of the program is to prevent the development of mental health problems among this group of children by providing support, information, and coping experiences. Method: This review is based on information from a systematic literature search in the databases Embase, Medline and Psykinfo, NORART Cochrane, Cristin, NORA, SCOPUS, and SweMed in addition to information from the program owner. Results: No studies examining the effect of the program were located. The program is well described in materials provided by the program owner. The program has a sound theoretical foundation in theories of psychoeducation, in addition to knowledge of risk and protective factors, which can impact the children’s psychosocial development in families where parents have mental health or substance abuse problems. The program owner does not offer training for group leaders, but will provide counselling and advice for anyone wanting to start new groups. . There is no system in place for securing implementation quality or monitoring the program fidelity. No evaluation of program effects has been conducted. Conclusion: The program is classified at evidence level 2- Theoretically based interventions.